Effect of time-based hot air drying method on chemical composition of jatropha zeyheir tea - Mutshekwa, Ndivhuho (University of Limpopo, 2017)
Tea is one of the most popular consumed beverages in the world, which has beneficial properties such as anti-oxidization, anti-carcinoma and preventing arteriosclerosis. The major essential components of catechins present in tea leaves, includes epigallocatechin gallate (EGCG), epigallocatechin (EGC), epicatechin gallate (ECG), epicatechin (EC), gallocatechin (GC) and catechin (C). Influence of time-based hot air drying method on chemical composition of the Jatropha zeyheri Sond, widely consumed in rural communities of Zebediela (Khureng village), Limpopo Province, South Africa, was investigated. Four treatments, namely; 0, 24, 48, and 72 hours, were arranged in completely randomised design (CRD), replicated five times. The study demonstrated that drying significantly increased total phenolic content, total antioxidant capacity and tannin content. It also demonstrated that drying significantly increased minerals elements; Mg, K, P, S, Al, Co, Mn, Si and Zn content and decreased Na, Ca and Ni and Zn quantities. Sodium-potassium ratio was very low across drying periods. Drying time did not significantly influence proximate chemicals; energy, protein, carbohydrates, ash and fibre content. Moisture and fat were significantly increased by drying period. Results of the study suggested that time-based hot air drying method improved the chemical composition of J. zeyheri, which has the potential of enhancing nutrition in marginal rural communities of Limpopo Province.
Thesis (M. Sc. (Agriculture)) --University of Limpopo, 2017
Keywords: Tea; Hot air drying method; Hot-air heating; Drying; Food -- Solar drying -- Equipment and supplies